A Study on Transnational Cultural Spaces in Bollywood Cinema - MUKUNDRAO MORE, Dr. DATTATRAYA (International Journal of Multidisciplinary Research and Studies, 2021)
Bollywood cinema has shifted from projecting anti-colonial understandings of moral and sexual female boundaries to emphasizing a more liberated, diasporic female figure, in the last three decades. The genre has traditionally found ways to restrict feminine sexuality within the confines of a nation-state, and only in a post-nation-state world, within transnational cultural spaces, can the female figure achieve some degree of liberation. The present research paper chronologically explores the development of depictions of females in the Indian diaspora in five major Bollywood films: Pardes, Dilwale Dulhania le Jayenge, Kabhi Khushi Kabhie Gam, Salaam Namaste and Love Aaj Kal.